EU labour markets and immigration connected to enlargement - Kari E.O. Alho (The Research Institute of the Finnish Economy (ETLA), 2002)
The EU economies and their labour markets will face new challenges in the near future as the Union enlarges to cover the CEE countries and the mobility of labour becomes free within the region. This paper first discusses estimates made on the likely magnitude of the coming immigration and then turns to derive some basic outcomes with respect to its impacts on real wages in the EU in the long run. We then discuss in a standard way the short-run net benefit from immigration, extend the analysis to the long-run steady state and carry out a numerical simulation of the effects of likely immigration, which raises the EU labour force by one per cent. We obtain the result that the net present value of the accumulated gain to the EU 15, measured by the rise of consumption in ratio to GDP, is very small. This result is in line with neutrality proposition predicted by theoretical reasoning, which prevails in the long run with respect to the effects of immigration. The last part of the paper deals with linkages between the social security system and immigration. Over time the short-run costs of adjustment, which are generally found to be quite small, are neutralised by the gains accrued from Enlargement. – – EU-maiden työmarkkinat joutuvat uuteen tilanteeseen, kun unioni laajenee Keski- ja Itä-Euroopan maihin ja työvoiman liikkuvuus vapautuu alueella. Tämä tutkimus esittelee ensin maahanmuuton laajuudesta tehtyjä arvioita ja johtaa sitten tuloksia sen pitkän ajan vaikutuksista reaalipalkkoihin EU:ssa. Tämän jälkeen keskustellaan tavanomaiseen tapaan lyhyen ajan nettohyödystä, joka liittyy maahanmuuttoon, ja laajennetaan analyysi pitkän ajan tasapainotilanteeseen. Tutkimuksessa laaditaan numeerinen simulointi maahanmuuton vaikutuksista, jonka tuloksena on, että kulutuksella mitatun hyödyn kumuloitu nykyarvo on pitkällä ajalla hyvin pieni EU 15:n nykyiselle väestölle ennustetun suuruisesta maahanmuutosta, joka lisää EU:n työvoimaa prosentilla. Tämä on sopusoinnussa yleisen tuloksen kanssa, jonka mukaan maahanmuuton vaikutukset ovat neutraalit pitkällä ajalla alkuperäiselle väestölle. Viimeinen osa tutkimusta käsittelee yhteyksiä sosiaaliturvajärjestelmän ja maahanmuuton välillä. Ajan mittaan lyhyen ajan kustannukset sopeutumisesta, jotka ovat yleensä melko pienet, neutraloituvat laajenemiseen liittyvillä hyödyillä.
Keywords: F22; F43; 330; Labour mobility; Immigration; EU Enlargement; Työvoiman liikkuvuus; maahanmuutto; EU:n laajeneminen; EU-Erweiterung; Internationale Arbeitsmobilität; Einwanderung; Arbeitsmarkt; EU-Staaten